Accelerate urban sustainability through policies and practices on the mobility system in Italy - Gaglione, Federica; Ayiine-Etigo, David Ania (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW251813317 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn="{"ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777844,"Tahoma",469769226,"Tahoma",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]}">Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility, and environment, thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation. Section aims at presenting the latest updates in the territorial and urban legislative sphere. The current challenges that today's cities have to face, from climate change to environmental and social ones, have led to urban planning being accompanied by the mobility system from a sustainable point of view. In turn, sustainable mobility constitutes that important link in the chain of development of cities. In this direction, the contribution explores in the first part how the scientific community is addressing the issue of sustainable mobility and what the new paradigms are, however, in the second part it focuses on the urban policies issued by the Italian government.